Communication Patterns and Strategies for the Spread of Milah Abraham in Palembang:: A Case Study of Recruitment and Prevention Strategies - Imam Haromain; Bukhori, K.A; Hasnah Nasution, Nurseri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The phenomenon of the spread of Milah Abraham in Palembang raises serious concerns about the integrity of Muslims in Indonesia because the teachings carried deviate from the mainstream of Islam and have the potential to create divisions in the Muslim community. This study aims to analyze the communication patterns used by the Milah Abraham group in spreading its teachings and recruitment strategies for members and sympathizers and evaluate prevention efforts made by various parties to maintain the stability and unity of the ummah. This research uses a qualitative method with a descriptive approach. Data were collected through field observations, in-depth interviews with Milah Abraham members, policymakers, and religious organizations, and documentation studies from various sources. The research findings show that the Milah Abraham group applies a systematic and practical communication pattern through a combination of digital media, personal meetings, and spiritual approaches that touch the emotional aspects of potential followers. Their recruitment strategy relies heavily on social networks and persuasive narratives packaged as informal da'wah. In the face of this spread, local Islamic organizations and stakeholders have pursued ahlusunnah wal jamaah-based da'wah as a counter-narrative measure. However, its effectiveness is still limited due to the lack of coordination and continuous religious education at the grassroots level. The original contribution of this research lies in mapping Milah Abraham's communication patterns and recruitment strategies contextually in the Palembang region, which has not been widely described in the literature. This research recommends the importance of strategic collaboration between the government, religious organizations, and the community in strengthening the understanding of the true Islamic faith through a more systematic, educative, and communicative approach.